SPATIAL DYNAMICS OF BUILT-UP LAND DEVELOPMENT BASED ON SLOPE GRADIENT IN TERNATE CITY, INDONESIA - Rifai, Ahmat; Rakuasa, Heinrich (Program Studi Pendidikan Geografi Universitas PGRI Sumatera Barat, 2024)
Ternate City in North Maluku, Indonesia, is experiencing rapid population growth and residential land development, with diverse topography and slopes that affect the expansion of built-up land. This study analyzed the development of built-up land in 1995 and 2025 based on slope levels using Landsat imagery and Digital Elevation Model (DEM) data. Results showed that built-up land expanded rapidly in the 8-25% slope zone (increased by 96.8-372%) and the >25% zone (+206.5%), indicating development pressure that drove urbanization to topographically challenging areas. Green land conversion (903.78 ha less) also affected the environmental balance, while water bodies remained stable (67.58 ha). The dominance of steep slopes >40% (3,013.36 ha) is a major challenge to sustainable development. The findings emphasize the need for a spatial approach based on integrated geomorphological analysis, particularly landslide risk mitigation in steep slope zones, while meeting settlement needs. The research makes an important contribution to the development of sustainable development strategies in island cities characterized by complex topography and limited flat land while offering a spatial-temporal evaluation model that can be applied in similar areas. Policy implications of the research include strengthening spatial regulations, applying special construction techniques in slope areas, and protecting protected areas to maintain the balance of the natural environment.